Peran Struktur Dewan Dalam Mempengaruhi Kinerja Pada Nilai Perusahaan Keluarga - Santi Yopie; Supriyanto Supriyanto; Budi Chandra (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2018)
The family company is synonymous with the characteristics to inherit its company from one generation to the next. The average family company can only survive and inherit up to third generation (Wahjono, Wajoedi, & Idrus, S, 2014). However, there are also have some family companies especially in the field of estate in Scotland that can last up to 400, 600 even 800 years (Belmonte, Seaman, & Bent, 2016). The culture and application of the board structure of each family company varies greatly. The purpose of this study was to determine the effect of board structure (CEO family / non-family, professional qualification, board size, and independent commissioner) on the value of the company in the family enterprise. This research method is analyzed by multiple linear regression on panel data that is 125 family company in BEI 2010-2014. The results of this study indicate that family firms run by non-family (professional) CEOs will be higher in corporate value than the family CEO. Professional qualifications have a significant negative influence on the value of the company. The size of the board has a significant positive influence on firm value. Independent commissioners have no significant influence on the value of family firms.